G13 Tilt positive pots (postural orthostatic tachycardia syndrome): a case series study. (25th October 2020) - Naz, A; Johal, S; Nair, P
Abstract : Introduction: PoTS (postural orthostatic tachycardia syndrome) is a condition of autonomic instability which causes significant tachycardia response on upright posture. It is also associated with a plethora of symptoms which can be very disabling for the child. A tilt positive PoTS is defined as a rise of heart rate more than 40 bpm (in the 12–19 year age group) within the first 12 minutes (criteria 1) or a sustained heart rate of more than 120 beats per minute in the first 10 minutes (Criteria 2) with no hypotension or other reasons for tachycardia. Aim: To do a retrospective analysis of 20 cases presenting to the PEC (Paediatrician with expertise in cardiology) clinic with positive diagnosis of PoTS on the head up tilt test (HUTT). Method: We did a retrospective analysis of children diagnosed with tilt positive PoTS, reviewing their clinical characteristics, symptomatology, results of tilt tests, treatment and outcome. Results: Of the 20 cases, there were 5 boys and 15 girls with an average age of presentation at 12.7 years. 75% of the cases presented around 12–15 years of age. The predominant symptoms were as follows: 4 of the patients also had a diagnosis of chronic fatigue syndrome (CFS). All patients had tilt tests (HUTT) of which fifteen satisfied criteria 1 and five satisfied criteria 2. The following medications were used: Outcome after medications: Discussion: PoTS is a multisystemic condition presenting typically in the adolescent girls with not many published studies in children. A tilt test helps to confirm the diagnosis and tailored management. Medications helps in symptomatic improvement in the majority with ability to resume education & activities. Children with deconditioning type of PoTS secondary to CFS often show poor response to medications.